2014
DOI: 10.3389/fmicb.2014.00151
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of the medicinal leech gut microbiota

Abstract: There are trillions of microbes found throughout the human body and they exceed the number of eukaryotic cells by 10-fold. Metagenomic studies have revealed that the majority of these microbes are found within the gut, playing an important role in the host's digestion and nutrition. The complexity of the animal digestive tract, unculturable microbes, and the lack of genetic tools for most culturable microbes make it challenging to explore the nature of these microbial interactions within this niche. The medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 81 publications
4
25
0
1
Order By: Relevance
“…16S rRNA V4 deep sequencing of the H. verbana ILF identified the same two dominant taxa as reported previously from 454 pyrosequncing of the 16S rRNA V6 region (21), 16S rRNA V3-V4 deep sequencing (17), and 16S rRNA clone library analysis (14) (Table 1). The ILF microbiota of H. verbana has been described as being dominated by Mucinivorans and Aeromonas with occasional Clostridial spp (14, 21).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…16S rRNA V4 deep sequencing of the H. verbana ILF identified the same two dominant taxa as reported previously from 454 pyrosequncing of the 16S rRNA V6 region (21), 16S rRNA V3-V4 deep sequencing (17), and 16S rRNA clone library analysis (14) (Table 1). The ILF microbiota of H. verbana has been described as being dominated by Mucinivorans and Aeromonas with occasional Clostridial spp (14, 21).…”
Section: Resultssupporting
confidence: 79%
“…16S rRNA V4 deep sequencing of the H. verbana ILF identified the same two dominant taxa as reported previously from 454 pyrosequncing of the 16S rRNA V6 region (21), 16S rRNA V3-V4 deep sequencing (17), and 16S rRNA clone library analysis (14) (Table 1). The ILF microbiota of H. verbana has been described as being dominated by Mucinivorans and Aeromonas with occasional Clostridial spp (14, 21). In the 36 animals tested, Mucinivorans and Aeromonas together accounted for 30.6 – 99.8% (median = 81.8%) of the sequences from the ILF (Table 1) with Proteiniclasticum making up an additional 0 – 63.4% (median when present = 10.8%, present in 69% of animals) and Fusobacterium making up an additional 0 – 28.3% (median when present = 11.5%, present in 47% of animals) (Table S2).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In particular, members of the Desulfovibrionaceae have recently been identified in the intestines of the Chinese roe deer Capreolus pygargus (Li, Zhang, Xu, et al, 2014) and Pekin/Muscovy ducks (Vasaï et al, 2014), the digestive tract of the medicinal leech Hirudo verbena (Maltz et al, 2014) and larvae of the beetle Holotrichia parallela (Huang & Zhang, 2013), faecal samples of Mexican black howler (Alouatta pigra) monkeys (Nakamura et al, 2011) and chickens from Czech poultry farms (Videnska et al, 2014), homogenates of the deep-sea sponge Geodia spp. (Brück et al, 2010) and Asbestopluma hypogea (Dupont, Corre, Li, Vacelet, & BourguetKondracki, 2013).…”
Section: Microbiome Of Animalsmentioning
confidence: 99%
“…Metagenomic studies have been conducted to get comprehensive information pertaining to leech gut microflora [28,70]. However, none of the study investigated the origin of the gut microflora, whether it is found in its habitat or not.…”
Section: Leech Gut and Body Surface Microfloramentioning
confidence: 99%